Stanisław Szozda (1950-2013) - Forgotten Legend of Polish Cycling - Daniel Bakota; Arkadiusz Płomiński; Beniamin Piksa (Jan Długosz University in Częstochowa, 2019)
Stanisław Szozda was born on September 25, 1950 in Dobromierz. During his career he represented the following clubs: LZS [RST - Rural Sports Team] Prudnik, "Legia" Warsaw, LZS "Zieloni" Opole and LKS [RSC - Rural Sports Club] "Ziemia Opolska". His greatest successes include, among others: twice 2nd place at the Olympic Games in Munich (1972) and Montreal (1976) in the 100-km team race; twice 1st place in the 100-km team race during the World Championships in Barcelona (1973) and Yvoir (1975); 1st place in individual classification of the Peace Race in 1974 and twice 1st place in team classification in Peace Race (1973 and 1974) and 1st place in Tour de Pologne (1971). He died on September 23, 2013. He was buried in the Osobowicki Cemetery in Wrocław in the Alley of the Meritorious.